2010
DOI: 10.3329/jhpn.v28i1.4528
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Dimensions of Depression in Bangladesh: A Qualitative Study in Two Villages of Matlab

Abstract: This article reports the results of a qualitative study conducted in two villages of Matlab to explore the cultural dimensions of depression. Participants included adult men and women with and without a history of depressive episode (n=42), formal and informal healthcare providers (n=6), and caregivers (n=2). Adults (n=10) with a history of depressive episode were selected from a 2005 survey conducted by ICDDR,B. A case vignette was used for eliciting local terms for depression, perceived causes, impact, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 20 publications
4
39
0
Order By: Relevance
“…For example, research among South Asian populations has shown that patients with depression usually link their depressive symptoms to different causes, for example any upsetting conditions, accidents or daily occurrence of events, unfavourable living conditions, financial problems or physical illness, and therefore consider it as a natural occurrence Chodhury, 1979;Farooq et al, 1995;Salim, 2010). In our own research, individuals with diabetes reported that problems with managing their diabetes led to feelings of low mood and hopelessness .…”
Section: Cultural Meanings Of Depressionmentioning
confidence: 73%
See 3 more Smart Citations
“…For example, research among South Asian populations has shown that patients with depression usually link their depressive symptoms to different causes, for example any upsetting conditions, accidents or daily occurrence of events, unfavourable living conditions, financial problems or physical illness, and therefore consider it as a natural occurrence Chodhury, 1979;Farooq et al, 1995;Salim, 2010). In our own research, individuals with diabetes reported that problems with managing their diabetes led to feelings of low mood and hopelessness .…”
Section: Cultural Meanings Of Depressionmentioning
confidence: 73%
“…The actual term 'depression' itself is often absent from the languages of many cultures or rarely used (Salim, 2010;Hamdi et al, 1997;Manson, 1995), or it is construed differently Bhugra and Mastrogianni, 2004;Lee, 1998).…”
Section: Cultural Meanings Of Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a qualitative study of the social construction of psychosocial health and its underlying causes in rural Bangladesh, local informants identified poverty as the main cause of poor psychosocial health (36). Poverty was defined as a chronic shortage of everyday necessities and/or the inability to meet daily needs.…”
Section: Discussionmentioning
confidence: 99%